Gambaran Tubuh dan Maskulinitas pada Pasien Kanker Payudara Pria: Implikasi bagi Keperawatan - Alexander, Alexander (Jurnal Keperawatan Universitas Jambi, 2025)
Male breast cancer (MBC) is rare yet under-addressed in oncology nursing, especially regarding body image and masculinity. This qualitative study explored how men with breast cancer in Medan, Indonesia, make sense of altered bodies, masculinity, and care needs. We conducted in-depth interviews with 14 adult MBC patients (post-surgery or on systemic therapy) at a tertiary center and community support settings. Data were analyzed using reflexive thematic analysis. Three themes emerged: (1) “A scar that questions manhood” (appearance concerns, mastectomy symbolism, sexual self-esteem), (2) “Between pink ribbons and blue identities” (stigma, misgendered spaces, delayed help-seeking), and (3) “What nursing care should look like for men” (gender-sensitive education, partner involvement, symptom self-management). Participants described tension between hegemonic masculinity ideals and survivorship, affecting disclosure, adherence, and quality of life. Findings suggest integrating gender-responsive assessment of body image, tailored education (e.g., tamoxifen adverse-effects counseling), and couple-focused supportive care. Results inform practice and policy, addressing a neglected subpopulation in oncology nursing.